Health Education at SDN 2 Sinarjaya Garut, in The Context of Introducing The Concept of Balanced Nutrition - Lubis, Novriyanti; Lindayani, Lindayani; Hidayat, Syaiful; Putri, Regina; budiman, Virly oktaviani; Santi, Rahmania; lisiawan, Bulan esaura; Patmawati7, Pipit; Fauzi, Rifki (Indonesian Journal of Community Empowerment (IJCE), 2024)
The extension activity was located at SD Negeri 2 Sirnajaya Garut with the theme "Optimizing Balanced Nutrition", carried out through collaboration by the Garut University Pharmacy PKM team and Padjadjaran University Pharmacy. Fulfilling balanced nutrition can be done by consuming food every day which must contain various nutrients in the type and amount according to needs. Other considerations needed are food variety, clean lifestyle, physical activity, and weight monitoring. This activity aims to increase children's understanding of the importance of balanced nutrition in supporting physical and cognitive growth. This activity involved grade 5 and 6 students with 43% male students and 57% female students. This activity includes pretest, posttest, providing educational material delivered through presentations, educational videos and distributing flyers as well as holding a question and answer session. Based on the data obtained, this counseling succeeded in increasing students' understanding from 67% to 78%, and students became aware of implementing a healthy lifestyle in order to obtain balanced nutrition.